Lao PDR and Vietnam Trade and Economic Linkages: Performance and Prospects - Walsh, John; Southiseng, Nittana; Trung, Nguyen Quang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 5E, 2019)
Lao PDR and Vietnam share an extensive land border and there are a number of points at which border crossings can be made and border trade conducted. The connectivity of these crossings is to be intensified by cross-border transportation infrastructure such as the Vientiane-Bolikhamsay-Vung Anh deep seaport railroad, which would facilitate exports from landlocked Lao PDR. Such infrastructure will improve existing Vietnamese investment in its western neighbour, where more than 400 projects worth more than US$5 billion have already been licensed in activities such as hydropower, industrial tree plantation and mining. This paper investigates the extent of Lao-Vietnamese border trade and cross-border investment and the prospects for the future in an international environment challenged by trade wars, volatility and global climate change. The strength of these links is noted and the bright prospects for future development acknowledged.